Accreditation in higher education. Organized and ed. by L.E. Blauch. [With contribs of J.B. Sanders, W.K. Selden, Th. Birch Wilkins a.o. With forew. by L.G. Derthick] (U.S. Government Printing Office, 1959)
With index,map and tabs. U.S. Department of Health, Education, and Welfare.